Comparative demography and diet breadth of Brazilian and African populations of the predatory mite Neoseiulus baraki, a candidate for biological control of coconut mite - Negloh, K.; Hanna, R.; Schausberger, P. (Elsevier, 2008)
Neoseiulus baraki Athias-Henriot (Phytoseiidae) is one of the few predators associated with the coconut mite Aceria guerreronis Keifer (Eriophyidae), the most damaging pest of coconut fruits in the Americas, Africa and more recently in Oman, Sri Lanka and parts of India. As Brazil is presently considered the putative origin of A. guerreronis, a large effort is presently underway to develop a classical biological control strategy for this pest in Africa and Asia. In this study, we investigated the life history of a Brazilian (NbBr) and a Beninese (NbBe) population of N. baraki on prey and non-prey diets under laboratory conditions (25 ± 1 °C 70–90% RH and 12:12 h L:D). Both populations were able to complete juvenile development and reproduce when feeding on A. guerreronis, Tetranychus urticae Koch eggs—a prey commonly used in the maintenance of phytoseiid mite colonies—and maize pollen. The two predators developed faster on A. guerreronis than on any other diet. The longest developmental time was recorded for NbBe on castor bean pollen (12.3 days), which also was not suitable at all for the development of NbBr. The longest developmental time of NbBr was 8.94 days on T. urticae eggs, whereas NbBe needed only 5.86 days to develop from eggs to adult stage on the same diet. For both populations, oviposition rate and longevity as well as demographic parameters were most favorable on A. guerreronis, the target prey. Intrinsic rate of natural increase (rm) and net reproductive rate (Ro) were significantly higher for NbBr (0.19 and 24.9) than for NbBe (0.16 and 18.0). Taken together, the life history data from this study predict that NbBr is a more specialized and efficient predator of A. guerreronis compared with NbBe. The ability of the latter to utilize alternative food types, however, predicts that it would be able to persist longer in coconut habitat in the absence of its primary prey A. guerreronis. Implications for the implementation of a sustainable control strategy against A. guerreronis are discussed.